MicroRNAs e seu papel no desenvolvimento e diferenciação sexual da Tilápia do Nilo (Oreochromis niloticus) - Giusti, Juliana [UNESP] (2015)
The Nile tilapia is a species of great importance in world aquaculture. Male specimens have increased growth compared with females, an important feature in fish production systems. Unfortunately, the mechanisms involved in the development and sexual differentiation in fish are still poorly understood. Several genes and miRNAs have been reported as influencing these processes, but its effective role remains unknown. Given the biological importance of miRNAs to embryonic development and sex determination, microRNomes were analyzed during development and in adult male and female of O. niloticus. Small RNAs libraries were generated from 3 and 5 dpf embryos, and brain and gonads of adult specimens, and sequenced using Illumina platform. Out of 194 miRNAs identified based on zebrafish database, 120 showed differential expression between male and female of O. niloticus. Additionally, 74 new miRNAs not detected in zefrafish database were found. Twenty-two miRNAs were tested by qPCR and five had their target candidate genes tested by luciferase reporter gene assay. The qPCR results showed that miR-10 family expression was high during the periods of 3 and 5dpf. Prediction software suggested that this family of miRNAs regulate the Hox genes family members. Therefore, were tested by qPCR and luciferase gene reporter assay, three Hox genes: Hoxa3a, HoxB3a and HoxD10a. The results showed that miR-10b have Hoxb3a and HoxD10a as target. In sex differentiation, the results of qPCR showed a high expression of miR-145-5p during the development of female embryos, while its possible target, Sox9, decreased. Moreover, the miR-181a expression decreased and his target gene, Cyp191a increased. The luciferase gene reporter assay validated the Cyp19a1 as a direct target of miR-181a, and Sox9 as a target of miR-145-5p. Our data suggest that, as in other vertebrates, Hox genes are extremely important in the development of Nile tilapia and are regulated by miR-10 ...